2009
DOI: 10.1159/000191284
|View full text |Cite
|
Sign up to set email alerts
|

Use of Sealants in Pancreatic Surgery: Critical Appraisal of the Literature

Abstract: Background/Aims: Fibrin sealants containing both fibrin and thrombin have been used to control bleeding, reinforce suture lines and enhance tissue healing. However, the literature provides contradictory results. Methods: A systematic literature search was performed to determine the use of fibrin sealants in pancreatic surgery. These articles were then critically appraised according to their methodologies, outcomes and conclusions. Results: Twenty-four studies were found, including 6 controlled randomized trial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 61 publications
1
17
0
2
Order By: Relevance
“…Several studies have shown the use of Tisseel fibrin sealant (Baxter Pharmaceuticals, Deerfield, IL, USA) injected into the duct or over the pancreatic staple line, though not harmful, demonstrated no significant decrease in the rate of fistula formation. 15 Meticulous dissection and oversewing of the pancreatic duct remain the gold standard for optimal outcome to minimize pancreatic leak.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown the use of Tisseel fibrin sealant (Baxter Pharmaceuticals, Deerfield, IL, USA) injected into the duct or over the pancreatic staple line, though not harmful, demonstrated no significant decrease in the rate of fistula formation. 15 Meticulous dissection and oversewing of the pancreatic duct remain the gold standard for optimal outcome to minimize pancreatic leak.…”
Section: Resultsmentioning
confidence: 99%
“…No method has proven superior for preventing postoperative fistulas or leaks. 19,20 Preservation of the pancreatic tail must be attempted in patients with injury to the right of the mesenteric vessels, where complete resection can lead to endocrine compromise in up to 50% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…Aplicações em cirurgia gastroenterológica incluem: prevenção de aderências peritoneais, cirurgia esplênica, hepatectomias, prevenção e tratamento de fístulas pancreáticas, enterocutâneas e anais 2,10,11,14,23 .…”
Section: Adesivos De Fibrinaunclassified
“…Têm sido utilizados em complicações de anastomoses pancreáticas com resultados satisfatórios. Entretanto, metanálise sobre o uso destes adesivos em cirurgia pancreática mostraram-se inconclusivos em decorrência da heterogeneidade e falta de evidência à sua utilização 10,16 .…”
Section: Adesivos De Fibrinaunclassified